IDDF2022-ABS-0173 Advanced colorectal neoplasia recurrence in high-risk individuals followed up at 1 year vs. 3 years: a cohort study. (2nd September 2022) - Huang, Junjie; Leung, Eman; Chun, Sam; Deng, Yunyang; Lam, Thomas; Tang, Raymond; Wong, Martin
Abstract : Background: A baseline result of advanced colorectal neoplasia should be followed up on within 1–3 years, according to current clinical guidelines. This study compared the recurrence rate of advanced colorectal neoplasia at 1 year vs. 3 years among subjects with advanced colorectal neoplasia detected and removed at baseline colonoscopy. Methods: From 2008 to 2018, we retrieved data from a large database in a Chinese population from eligible patients with advanced colorectal neoplasia polypectomised and receiving surveillance colonoscopy after 1 or 3 years. At follow-up colonoscopy, the outcome variables were recurrence of advanced adenoma and advanced neoplasia, respectively. The association between length of surveillance and the outcome variables was investigated using a binary logistic regression model that controlled for colorectal cancer risk factors such as age, gender, smoking, alcohol consumption, body mass index, and chronic disorders. Results: From our dataset, we included 147, 270 participants who had a baseline colonoscopy. They were on average 69.3 years old, with male individuals accounting for 59.7% of the total. Advanced colorectal neoplasia recurrence rates were 7.57 percent and 7.74 percent after one year and three years, respectively (crude odds ratio=1.025, 95 percent C.I.0.914 to 1.151, p=0.670). Individuals who had a 3-year surveillance colonoscopy did not have a substantially greater recurrence rate of advanced colorectal neoplasia than those who had a 1-year surveillance colonoscopy (adjusted odds ratio=1.005, 95 percent C.I. 0.878 to 1.149, p=0.940). Conclusions: There is no statistically significant difference in the recurrence of advanced colorectal neoplasia between those who had a workup at one year and those who had a workup at three years. After baseline advanced colorectal neoplasia was polypectomised, our findings support a 3-year surveillance interval.